A new generate carrier for THz communication by the nonlinear microring resonator systems - P. Eakkapan; S. Somkuarnpanit; N. Pornsuwancharoen; P.P. Yupapin (My University, 2012)
This paper presents the simulation results of light pulse traveling within a microring resonator system that have shown the optimize results with various applications. The design system consists of a nonlinear microring resonator system incorporating an add/drop filter. The input is bright soliton pluse, whereas the suitable simulation parameters are input power, pulse width, ring radii are 5-10 μm and the material refractive indices (κ) are 0.10-0.97. The potential applications for new technique for THz communication system is 0.19 THz by laser sources from microring and nanoring resonator device.
Keywords: Nanoring; Photonic and Optical Devices